Biological and cultural variable of sexuality in the perception of college students - León-Donayre, Ramón (2000)
The purpose of this research is to determine the value given by adolescents and young adults to a set of biological and social variables of their behaviors and attitudes towards sexuality. The following variables were considered: mother’s and father’s images, religion, fear of “what are they going to say”, sexual impulse, sexual education received in school, friends, sexual curiosity, risk of AIDS, self-control, and response to particular situations. The set of variables included the value given to men or women who had had sexual relations before marriage, sexual stereotypes of people of the Peruvian coast, the Andes and the Amazon. The results showed that men and women give different value to the sexual dimension in their lives.